Problems in Upper Brantas Watershed Governance: A Case Study in Batu, Indonesia - Tri Sulistyaningsih; Sulardi Sulardi; Sunarto Sunarto (Jurnal Studi Pemerintahan, 2017)
The damage to Brantas River Basin (Watershed) has been increasingly critical due to forest encroachment and land use ignoring the rules of soil and water conser- vation. This study aims to examine the problems in the management of upper Brantas Watershed in Batu City, Indonesia. The method used in this research was descriptive-qualitative and the data were collected using participative observa- tion in the field, in-depth interviews with the community of Brantas Watershed- Caring Farmer Group (Komunitas Petani Penyelamat Daerah Aliran Sungai Brantas- KPPDAS), discussion with experts, and Focus Group Discussion (FGD). This paper succeeded in extracting information about the fundamental problems causing damage to Brantas Watershed in Batu City. Those fundamental problems con- sisted of pragmatic behavior and ways of thinking of land use in the upper wa- tershed of Brantas, government policies that were not aligned to the upstream conservation of Brantas Watershed, the low public awareness to actively partici- pate in the upstream conservation of Brantas Watershed. Therefore, the man- agement of upper Brantas Watershed needs to strengthen the cooperation (part- nership) among stakeholders to savejointly the upstream of Brantas River Basin or Watershed.